PLD.20 Postpartum haemorrhage: immediate management and failures of adherence to guidelines and prompt actions. (9th June 2014) - Briley, A; Tydeman, G; Seed, P; Waterstone, M; Tribe, RM; Sandall, J; Bewley, S
Abstract : Background: Postpartum haemorrhage (PPH) remains a common cause of maternal morbidity globally. Widely available treatments exist to treat this common complication, yet incidence and associated morbidities are rising in resource rich countries. Reasons are likely to be complex and multifactorial. Traditional and novel risk factors have been implicated, but the impact of changing practice and guidelines require assessment. Method: Data were collected for 10, 213 women giving birth in two south England maternity services 2008–2009. Information imported from NHS databases. Cases were randomly selected according to weighted sampling strategy for scrutiny of all maternity records. Details of management of the third stage and actions in response to PPH were collected. Results: Third stage management Conclusion: Despite NICE, RCOG and local guidelines Syntometrine® remains commonly used. High incidence of IV treatments may reflect caesarean births. Actions known to be effective at treating PPH may not be promptly instigated.